2019
DOI: 10.1016/j.jallcom.2018.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Structural, elastic, electronic, thermodynamic, and optical properties of layered BaPd2As2 pnictide superconductor: A first principles investigation

Abstract: BaPd 2 As 2 belongs to 122 pnictide group, famous for exhibiting superconductivity at high temperatures and other electronic correlations. Unlike the 122 iron arsenides, BaPd 2 As 2 exhibits superconductivity at low temperature when realized in theThCr 2 Si 2 type structure (I4/mmm). We have performed density functional theory (DFT) based calculations to investigate the structural, elastic, electronic, thermodynamic, and optical properties of BaPd 2 As 2 in this study. The structural, elastic, and the band str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 45 publications
7
28
0
Order By: Relevance
“…The values reported in Table 2 are all positive and satisfy all the above four criteria, hence proving that this tetragonal compound is stable. C 11 > C 33 as seen from Table 2 , implying that the crystal is more stiff along 100 and 010 axes, results which are in agreement with the study on a similar iron pnictide BaPd 2 As 2 [ 25 ]. C 12 – C 44 gives the Cauchy pressure, which, if positive, makes the compound ductile.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The values reported in Table 2 are all positive and satisfy all the above four criteria, hence proving that this tetragonal compound is stable. C 11 > C 33 as seen from Table 2 , implying that the crystal is more stiff along 100 and 010 axes, results which are in agreement with the study on a similar iron pnictide BaPd 2 As 2 [ 25 ]. C 12 – C 44 gives the Cauchy pressure, which, if positive, makes the compound ductile.…”
Section: Resultssupporting
confidence: 90%
“…C 12 – C 44 gives the Cauchy pressure, which, if positive, makes the compound ductile. From Table 2 , the Cauchy pressure is positive; hence the material is ductile, a result similar to that of a related iron pnictide [ 25 ].…”
Section: Resultsmentioning
confidence: 68%
“…The mechanical properties we obtained from the computation are summarized in Table 1 below. The Poisson's ratio was found to be ∼0.32 at absolute zero temperature, our result compared well to a value of 0.302 for other families of Pnictides [41], the difference may be as a result of varying atoms present in the two compounds and a slight difference in the crystal structure. This value further confirmed that EuFe 2 As 2 is a stable and metallic [45, ] Other Pnictides such as SrFe 2 As 2 have a Poisson's ratio of ∼0.48 upon application of pressure [47], which causes the lattice parameters to change.…”
Section: Resultssupporting
confidence: 84%
“…Other minor curves are left out in the illustration since their contribution to the Partial Density of States was minimal. The density of states of other Pnictides shows similar gaps [41].…”
Section: Resultsmentioning
confidence: 87%
“…This reflects strongly the layered structural and bonding features of TiNX. The machinability index of TiNX compares favorably to that for other layered ternaries [14,16,17].…”
Section: Discussionmentioning
confidence: 89%